Effect of flexing and massage on in vivo human skin penetration and toxicity of zinc oxide nanoparticles. (May 2016) - Leite-Silva, Vânia R; Liu, David C; Sanchez, Washington Y; Studier, Hauke; Mohammed, Yousuf H; Holmes, Amy; Becker, Wolfgang; Grice, Jeffrey E; Benson, Heather AE; Roberts, Michael S
Aim: We assessed the effects of flexing and massage on human skin penetration and toxicity of topically applied coated and uncoated zinc oxide nanoparticles (˜75 nm) in vivo .Materials & methods: Noninvasive multiphoton tomography with fluorescence lifetime imaging was used to evaluate the penetration of nanoparticles through the skin barrier and cellular apoptosis in the viable epidermis.Results: All nanoparticles applied to skin with flexing and massage were retained in the stratum corneum or skin furrows. No significant penetration into the viable epidermis was seen and no cellular toxicity was detected.Conclusion: Exposure of normal in vivo human skin to these nanoparticles under common in-use conditions of flexing or massage is not associated with significant adverse events.